The effect of a 12-week resistance training intervention on leukocyte telomere length. Issue 6 (June 2020) - Nickels, Matt; Mastana, Sarabjit; Hunter, David; Denniff, Matthew; Codd, Veryan; Akam, Elizabeth
Abstract: Telomere dynamics are an active biological process and positive lifestyle factors such as exercise are proposed to potentiate their length. The aim of this study was to investigate the effect of a low-resistance, high-repetition resistance training intervention on leukocyte telomere length (LTL) and associated health parameters. 23 sedentary middle-aged adults volunteered for this study (16 female/7 male; age = 51.5 ± 4.9 years) and performed two one-hour sessions of Les Mills BODYPUMP™ per week for 12 weeks. Outcome measures were taken at baseline, after the training intervention and at 12-month follow-up. LTL remained unchanged following the training intervention (pre 0.819 ± 0.121 vs post 0.812 ± 0.114, p = 0.420), despite a borderline significant increase in hTERT expression (p = 0.050). Circulating levels of tumour necrosis factor alpha were reduced after the intervention (p = 0.001). At 12-month follow-up, subjects who returned to a sedentary lifestyle (n = 10) displayed shorter telomeres compared to their pre (p = 0.036) values. In conclusion, no changes were observed in LTL following the 12-week training intervention, despite improvements in molecular parameters associated with telomere dynamics. It appears continued long-term exercise (>12 months) is necessary to preserve LTL in previously sedentary individuals. Abstract : Molecular Dynamics; Aging; Physical Activity; Human Genetics; Physiology; Exercise; Tumour necrosis factor alpha; Strength; BODYPUMP